2019
DOI: 10.1039/c8ra10352f
|View full text |Cite
|
Sign up to set email alerts
|

The effect of foam quality, particle concentration and flow rate on nanoparticle-stabilized CO2 mobility control foams

Abstract: CO2 foam is regarded as a promising technology and widely used in the oil and gas industry, not only to improve oil production, but also to mitigate carbon emissions through their capture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…This was because the texture of the foam generated at a low-quality regime was finer, with smaller trapped gas bubbles resulting in a lower pressure drop. This finding agreed with the literature, 39,68 which categorized foam texture into different types based on the gas bubble size. Fine foam possesses a small bubble, whereas coarse foam has much larger gas bubbles that collapse promptly.…”
Section: Effect Of Foam Quality (Phase 3)supporting
confidence: 93%
See 3 more Smart Citations
“…This was because the texture of the foam generated at a low-quality regime was finer, with smaller trapped gas bubbles resulting in a lower pressure drop. This finding agreed with the literature, 39,68 which categorized foam texture into different types based on the gas bubble size. Fine foam possesses a small bubble, whereas coarse foam has much larger gas bubbles that collapse promptly.…”
Section: Effect Of Foam Quality (Phase 3)supporting
confidence: 93%
“…Therefore, the fine foam produced in a low-quality regime is more stable and stronger than the coarse foam generated in a high-quality regime. Additionally, as the bubbles get larger, they are vulnerable to more collisions and interactions, resulting in slightly coarser foams …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that increasing the gas flow rate can decrease foam generation time, suggesting faster bubble formation. 69 Additionally, lower gas flow rates might necessitate the use of additives like sodium carboxymethylcellulose to prevent bubble collapse and enhance foamability. 70 However, excessively high gas flow rates can also negatively impact foam stability.…”
Section: Effect Of Gas Flowmentioning
confidence: 99%